1990
DOI: 10.1002/1520-6629(199004)18:2<141::aid-jcop2290180206>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Victimization among homeless women: Implications for service delivery

Abstract: This article focuses on the experience of victimization among a representative sample of 141 homeless women interviewed in a single‐adult shelter in New York City. The frequency of victimization experiences, specifically aggressive sexual and physical assault, was high. Twenty‐one women reported being raped, 42 women reported both rape and physical abuse, and 62 women reported physical abuse without sexual abuse. Shelter women reporting frequent experiences were likely to experience high levels of depressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 24 publications
4
94
1
1
Order By: Relevance
“…Victimization increases risk of psychological distress, psychiatric problems, and substance abuse, which can persist for years after the event [11,33], as well as impaired social cognition, poor understanding of social roles, and hostile behavior, attribution, and problem solving style [34]. Homeless youth with traumatic experiences, including adverse experiences within the family, are at increased risk for subsequent victimization [35,36].…”
Section: Experiences Of Victimizationmentioning
confidence: 99%
“…Victimization increases risk of psychological distress, psychiatric problems, and substance abuse, which can persist for years after the event [11,33], as well as impaired social cognition, poor understanding of social roles, and hostile behavior, attribution, and problem solving style [34]. Homeless youth with traumatic experiences, including adverse experiences within the family, are at increased risk for subsequent victimization [35,36].…”
Section: Experiences Of Victimizationmentioning
confidence: 99%
“…26 In this paper we examine the degree to which psychiatric and substance problems and victimization place poor, New…”
mentioning
confidence: 99%
“…Of 961 homeless women, just over a third (34%) reported experiencing major physical violence in the past year, and half of those women reported experiencing more than one assault during that time . D'Ercole and Struening (1990) found that women in a sample of 141 homeless women in New York City had experienced various types of violence (21 had been raped, 62 had experienced physical abuse, and 42 had experienced rape and physical abuse). These rates are higher than for women in the general population.…”
Section: Homelessness: An Important Exosystem Factormentioning
confidence: 99%
“…D'Ercole and Struening (1990) note that beyond providing housing, ending homelessness requires that the mental health needs of women who have endured homelessness be addressed. Additionally, the structure of how these systems work should be designed in such a way that does not harm women further (D'Ercole & Struening, 1990;Ingram et al, 1996). Special attention needs to be given to promoting women's feelings of security and physical safety.…”
Section: Prevention and Policy Implicationsmentioning
confidence: 99%